Vulnerability Mapping for Methane Emissions and Mitigation Strategies in Lokoja Metropolis - Agada, D. u.; Guma, E. P.; Salau, O. Z. (Journal of Spatial Information Sciences, 2025)
Methane emissions is a potent contributor to climate change, and this is notably high in Lokoja, Nigeria, particularly in areas undergoing rapid urbanization, industrialization, and slum growth. The aim of this study is vulnerability mapping to show areas with likely sources of Methane emissions in Lokoja Metropolis. The objectives of the study include; mapping of susceptible areas and the sampling of measures to mitigate causes of global warming in the study area. The study leveraged on remote sensing data to identify the possible methane source areas and the administration of questionnaires to sample the sources and mitigation strategy of methane emission was deployed. The study generated a map highlighting potential methane emission hotspots. The findings pinpointed several areas like Felele, Sarki-noma, Adankolo, Ganaja and Kabawa, that exhibited slum-like characteristics that is contributing to methane emissions. To mitigate these emissions and foster sustainable development, the study recommended that there is the need for the Environmental sanitation agency to take proactive steps in ensuring that the environment is kept clean and free from pollution. More so, Planning Authorities should ensure that building plans are followed before, during and after construction especially laying emphasis on toilet provision to stop open defecation.